1998
DOI: 10.1302/0301-620x.80b5.0800781
|View full text |Cite
|
Sign up to set email alerts
|

Operative reconstruction after transverse rupture of the tendons of both peroneus longus and brevis

Abstract: Rupture of the tendons of both peroneus longus and peroneus brevis results in considerable disability. We have performed transfer of flexor digitorum longus (FDL) to peroneus brevis in two patients with lateral instability of the hindfoot due to chronic transverse tears of both tendons for which end-to-end repair was not possible. Both patients had excellent function when reviewed after eight and six years, respectively, with no symptoms. CT showed a normal appearance of the FDL in both patients, but the peron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 19 publications
0
37
1
Order By: Relevance
“…Peroneus brevis tears are common [3–14]. Cadaver studies indicate that the incidence ranges from 11% to 37% [10, 11, 14].…”
Section: Peroneus Brevismentioning
confidence: 99%
“…Peroneus brevis tears are common [3–14]. Cadaver studies indicate that the incidence ranges from 11% to 37% [10, 11, 14].…”
Section: Peroneus Brevismentioning
confidence: 99%
“…Therefore, accurate detection and confirmation on images are imperative. [1][2][3][4][5][6] Ultrasonography allowed a diagnosis of complete transverse rupture of the peroneus longus tendon. The fluidfilled tendon sheath and the discontinuity of the tendon on ultrasonography led to the diagnosis of peroneus longus rupture.…”
Section: Discussionmentioning
confidence: 99%
“…8 Rupture of the peroneus longus can occur with spontaneous rupture of the tendon occurring through a fracture or posterior dislocation of the os peroneum. 4 The os peroneum is a sesamoid bone that exists within the peroneus longus tendon in the region of the cuboid tunnel. It is present in 20% of adults and is bilateral in 60% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Others have recommended tendon transfer, which has also been reported with satisfactory results. 7 Although both of these offer relatively simple and perhaps less technically demanding options, autologous tendon transfers suffer from the pitfalls of donor site morbidity and, in our anecdotal experience, have negatively affected normal gait mechanics.…”
mentioning
confidence: 99%
“…Numerous authors have reported satisfactory results of peroneal tendon reconstructions with autograft transfer. 7,30,37 More recently, the use of an acellular dermal matrix has been reported. 26 We have previously published our operative technique for allograft reconstruction.…”
mentioning
confidence: 99%